Antibacterial Chitosan Nanofiber Thin Films with Bacitracin Zinc Salt - Kumamoto, Kazutaka (Polymers (Basel), 2021)
Chitosan nanofiber has a highly uniform structure of 20–50 nm in diameter and shows high dispersibility in water due to its submicron size and high surface-to-volume ratio. The stacked nanofibers film is useful for breathability because it has a gap with a size of several tens of nm or more. However, the chemical bonds between the nanofibers cannot be broken during use. In this study, the thin films were obtained by filtration of chitosan nanofibers and 3-glycidoxypropyltrimethoxysilane (GPTMS) mixture. The addition of GPTMS changed the wettability, mechanical property and stability in water of the thin films. Bacitracin zinc salt (BZ) has been used for the localized dermatological medicines and loaded in the films. BZ interacted electrostatically with the thin films matrix and the release of BZ was controlled by the amount of GPTMS. A higher released amount of BZ showed higher antibacterial effects toward S. aureus. The film was also tested their toxicity by L929 fibroblasts. The release of less than 11.9 μg of BZ showed antibacterial effects, but were not toxic for fibroblast cells.